2001
DOI: 10.1074/jbc.m008207200
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Status Selects for Spontaneous Somatic Androgen Receptor Variants That Demonstrate Specific Ligand and Cofactor Dependent Activities in Autochthonous Prostate Cancer

Abstract: We have used the autochthonous transgenic adenocarcinoma of mouse prostate (TRAMP) model to investigate the relationship between somatic mutation in the androgen receptor (AR) and the emergence of androgenindependent prostate cancer. Here we report the identification, isolation, and characterization of distinct classes of AR variants from spontaneous prostate tumors in the TRAMP model. Using cDNA cloning, single stranded conformation polymorphism and sequencing strategies, 15 unique somatic mutations in the AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
108
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 38 publications
6
108
0
Order By: Relevance
“…In this study, AR expression was reduced in epithelial and stromal cells 1-week postcastration, which was the normal short-term response to castration in TRAMP mice. Sometimes AR was not detected in tumour cells, which was possibly because of lack of AR expression or the expression of a mutated AR [22,23]. In this study, AR expression was significantly lower in tumours from the early castration group than in the sham-castrated or delayed castration groups, and the tumours in the delayed castration group showed less AR expression than in the sham-castrated group.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, AR expression was reduced in epithelial and stromal cells 1-week postcastration, which was the normal short-term response to castration in TRAMP mice. Sometimes AR was not detected in tumour cells, which was possibly because of lack of AR expression or the expression of a mutated AR [22,23]. In this study, AR expression was significantly lower in tumours from the early castration group than in the sham-castrated or delayed castration groups, and the tumours in the delayed castration group showed less AR expression than in the sham-castrated group.…”
Section: Discussionmentioning
confidence: 67%
“…Similar mutations in the same region have been reported. 29,30,[39][40][41] The type of treatment given was also shown to influence the kind of mutation seen. 42 Since reports have shown that mutations are present in 20-40% of the advanced PCAs before therapy, 30,31 it could be hypothesized that the mutations were not induced by therapy but were pre-existent.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…[10][11][12] AR variants identified in clinical prostate tumors typically exhibit promiscuous activation by nonandrogenic ligands and/or enhanced transactivation capacity due to altered interactions with coregulators. 13 The prototypical example of AR promiscuity is AR-T877A (T857A in mice), a variant expressed in the LNCaP prostate cancer cell line that is activated by estrogen, progesterone and the AR antagonist, hydroxyflutamide, in addition to androgens. 14 The AR contains a highly variable amino-terminal domain (NTD) essential for receptor stabilization 15,16 that also regulates its transcriptional activity by providing an interaction surface for key prostate-specific co-regulators and the transcriptional machinery.…”
mentioning
confidence: 99%
“…17 The AR-NTD signature (ANTS) sequence, composed of amino acids 234-247 (229-242 in mice), is the most evolutionarily conserved region of the AR but, interestingly, is not found in related steroid receptors. 13,18 Mutations have been identified proximal to the ANTS sequence in clinical prostate cancers 2 and within or near this sequence in castrate-resistant tumors arising in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. 2,13 Two AR variants arising from such mutations, E231G and A229T, display increased basal activity and response to androgenic and non-androgenic ligands compared to wild-type AR (wtAR).…”
mentioning
confidence: 99%
See 1 more Smart Citation